2019
DOI: 10.1038/s41467-019-10240-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-selective ligand-driven separation of strategic actinides

Abstract: Metal ion separations are critical to numerous fields, including nuclear medicine, waste recycling, space exploration, and fundamental research. Nonetheless, operational conditions and performance are limited, imposing compromises between recovery, purity, and cost. Siderophore-inspired ligands show unprecedented charge-based selectivity and compatibility with harsh industry conditions, affording excellent separation efficiency, robustness and process control. Here, we successfully demonstrate a general separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…When another metal that competes with Eu 3+ for 343-HOPO binding is added to the system, the intensity of the emission spectrum of [ Structural chemistry of rare earth complexes with 343-HOPO. While the solution chemistry of 343-HOPO and its use in a variety of applications such as actinide decorporation and separations 37,38 , post-MRI chelation therapy 39 , or 89 Zr PET imaging 40 is increasingly well-characterized, the structural chemistry of this chelator, with trivalent metals in particular, remains largely unexplored. Daumann et al reported the first crystal structure featuring 343-HOPO and Eu 3+ in 2015 41 , and this remained the only published structure featuring 343-HOPO and a trivalent metal until this study.…”
Section: Resultsmentioning
confidence: 99%
“…When another metal that competes with Eu 3+ for 343-HOPO binding is added to the system, the intensity of the emission spectrum of [ Structural chemistry of rare earth complexes with 343-HOPO. While the solution chemistry of 343-HOPO and its use in a variety of applications such as actinide decorporation and separations 37,38 , post-MRI chelation therapy 39 , or 89 Zr PET imaging 40 is increasingly well-characterized, the structural chemistry of this chelator, with trivalent metals in particular, remains largely unexplored. Daumann et al reported the first crystal structure featuring 343-HOPO and Eu 3+ in 2015 41 , and this remained the only published structure featuring 343-HOPO and a trivalent metal until this study.…”
Section: Resultsmentioning
confidence: 99%
“…27,30,39,40 Extended aging of U IV in aqueous media can also lead to changes in metal-ion speciation; 35,40 however, this was not observed here via UV−vis or investigated via other techniques, which suggests the U IV -343-HOPO complex is very stable, a likely result of the thermodynamic benefits of the chelate effect and the known selectivity of 343-HOPO for tetravalent metal cations. 41 To improve our understanding of U IV and U VI coordination by the 343-ligands, we turned to X-ray absorption spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[3] The separation processes of tetravalent ions such as Zr(IV) and Hf(IV) have offered a paradigm shift in the production of strategic elements. [4][5][6] Hafnium and zirconium are hard metals, and their cations are highly oxophilic with a strong Lewis acid character. Thus, the metal-ligand bond is highly ionic, and the geometric arrangement results in the need to minimize electron-electron repulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, PSI-MS transfers ions from the condensed to the gas phase, whereas DFT calculations provide detailed information regarding their stability and structure. Because the separation/extraction processes occur in a nitric medium, [2,6,9] the proposed acidic medium used herein contains high contents of nitrate (NO 3 À ) and fluoride (F À ) to simulate the conditions of alternatives extraction routes. [10][11][12] The identification of these species may suit as a model to understand, at the molecular level, one step of the processes that are of interest to the nuclear industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation